Research on the Restructuring of Social Assistance Social Work Course Content in the Context of the Party Committee’s Social Work Department - Su, Min; Chen, Shihai; Fu, Wenjing (Journal of Educational Research and Policies, 2025)
Against the backdrop of the establishment of the Social Work Department of the Party Committee and the “stratified and classified social assistance” policy, the social assistance social work curriculum has been given new responsibilities and missions. However, traditional social assistance courses face multiple dilemmas, including structural discontinuity with the “stratified and classified” assistance system, disconnection from the concept of developmental social assistance, and field failure. To respond to the new requirements for social work talents put forward by the establishment of the Social Work Department of the Party Committee, the curriculum reconstruction aims to cultivate three core competencies: political literacy and policy transmission ability, resource integration and collaborative service ability, and data empowerment and intelligent assistance ability. The curriculum content of the social assistance social work course is systematically reconstructed, a competency-oriented course module is constructed, a practical teaching system of “government-school collaboration” is created, and a multi-faceted process-based course evaluation system is established. This will effectively enhance students’ comprehensive practical ability to cope with complex assistance tasks in the new governance structure coordinated by the Social Work Department of the Party Committee.